1992
DOI: 10.1016/0550-3213(92)90536-k
|View full text |Cite
|
Sign up to set email alerts
|

Exact black string solutions in three dimensions

Abstract: A family of exact conformal field theories is constructed which describe charged black strings in three dimensions. Unlike previous charged black hole or extended black hole solutions in string theory, the low energy spacetime metric has a regular inner horizon (in addition to the event horizon) and a timelike singularity. As the charge to mass ratio approaches unity, the event horizon remains but the singularity disappears.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
395
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(411 citation statements)
references
References 19 publications
16
395
0
Order By: Relevance
“…Now, the entropy of the fivedimensional black hole (6) in the extremal limit is S = 2π 2 r 2 1 r 5 /4G 5 . Substituting the corresponding two-dimensional quantities into it, in particular G 5 = 2π 2 r 3 5 G 2 , we again find agreement with the formula (20) derived in [25].…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Now, the entropy of the fivedimensional black hole (6) in the extremal limit is S = 2π 2 r 2 1 r 5 /4G 5 . Substituting the corresponding two-dimensional quantities into it, in particular G 5 = 2π 2 r 3 5 G 2 , we again find agreement with the formula (20) derived in [25].…”
supporting
confidence: 82%
“…(This type of transformation is, in fact, not new. It was also found by Horowitz and Welch [19], when they showed that the BTZ black hole is T-dual to a class of asymptotically flat three-dimensional black strings [20].) By exploiting this U-duality between the three-and higher-dimensional black holes, Sfetsos and Skenderis [21] have recently argued that Carlip's method in effect provides a way, if somewhat indirect, of microscopically computing the entropy of the four-and five-dimensional black holes.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…(23). This clearly shows that, at r = 0, the x direction collapses and therefore we have to abandon the wormhole interpretation.…”
Section: Angular Magnetic Field Solutionsmentioning
confidence: 90%
“…This is remarkable because, in particular, duality is exchanging singularity↔horizon [19]. Moreover, in simple extensions of this geometry to 3D, the geometry is a black string (in the sense that the singularity is not point like but one-dimensional) [20], [15] which is no longer selfdual. It is dual to another black string where now the singularity of one geometry is mapped to a regular surface in the asymptotically flat region of the other geometry and on which, contrary to the horizon, classical computations are dominant.…”
Section: Abelian T -Dualitymentioning
confidence: 99%